2020
DOI: 10.1088/1742-6596/1567/4/042006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of students’ competence in chemistry cognitive test construction based on revised bloom’s taxonomy

Abstract: The test is one of the tools used to measure the cognitive competence of students. The ability to develop tests is one of the competencies teachers and prospective teachers must possess. Revised Bloom’s Taxonomy combines cognitive levels and types of knowledge in constructing cognitive tests. The subject of this study was a postgraduate student in the Chemistry Education Study Program of Makassar State University consisting of 25 people. The purpose of this study was to analyze the students competence in const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…All of the studies used written methods to assess the knowledge. Su cient written tests are considered to examine knowledge alone [94]. However, to evaluate the high levels of Bloom's taxonomy, it is suggested that these evaluations should not be focused on a questionnaire because it may be challenging to deal with the actual situation of the student [43].…”
Section: Table4 Medical Educationmentioning
confidence: 99%
“…All of the studies used written methods to assess the knowledge. Su cient written tests are considered to examine knowledge alone [94]. However, to evaluate the high levels of Bloom's taxonomy, it is suggested that these evaluations should not be focused on a questionnaire because it may be challenging to deal with the actual situation of the student [43].…”
Section: Table4 Medical Educationmentioning
confidence: 99%
“…Menganalisis memang lebih mudah disbanding mengevaluasi dan mencipta (Wijaya et al, 2019) Proses berpikir mengevaluasi mendapatkan presentase total kurang dari 50% yakni 46,91% sehingga masih dianggap rendah dalam kategori cukup (Retnawati, 2015). Proses berpikir mengevaluasi paling banyak berkaitan dengan dimensi pengetahuan konseptual dan prosedural (Ramlawati et al, 2019). Pada dimensi konseptual didapatkan hasil 48,15% yang mengakomodasi siswa dapat mencapai proses mengevaluasi, siswa menghubungkan keterkaitan antarbagian konsep yang diterima baik berupa model, teori, maupun struktur akan lebih banyak mengevaluasi apakah konsep yang didapat benar atau salah.…”
Section: Tabel 3 Data Proses Berpikir Siklusunclassified
“…Mencipta merupakan proses berpikir yang sulit dicapai oleh siswa, hal tersebut dapat terjadi karena guru tidak memberikan latihan yang mengakomodasi siswa untuk menciptakan suatu produk atau ide (Syahida & Irwandi, 2015). Proses berpikir mencipta paling banyak berkaitan dengan dimensi pengetahuan prosedural (Ramlawati et al, 2019). Pada dimensi pengetahuan konseptual didapatkan hasil sebesar 40,74% dapat mengakomodasi siswa mencapai proses berpikir mencipta, siswa yang memiliki pengetahuan secara umum atau abstrak yang berupa konsep serta kesadaran untuk menyusun konsep tersebut menjadi suatu hasil berupa produk dapat sampai ke tahap proses berpikir mencipta (Yusnaeni et al, 2017).…”
Section: Tabel 3 Data Proses Berpikir Siklusunclassified
“…Assessment is a systematic activity consisting of gathering information about the learning process and student learning outcomes with the aim of making decisions based on certain provisions (Sudarsana et al 2020). The assessment process in learning is very important so that it cannot be separated from learning activities (Ramlawati et al 2020). The main purpose of the assessment is to determine the extent to which the desired learning outcomes have been achieved.…”
Section: Introductionmentioning
confidence: 99%